2023
DOI: 10.3390/languages8030161
|View full text |Cite
|
Sign up to set email alerts
|

Creaky Voice in Chilean Spanish: A Tool for Organizing Discourse and Invoking Alignment

Abstract: This study relies on an interactional, conversational–analytic approach to elucidate what meanings Chilean Spanish speakers convey via creaky voice quality in informal conversations. Highly creaky utterances produced by 18 speakers were derived from a larger corpus of sociolinguistic interview speech from Santiago, Chile, and examined via an interactional approach that accounted for how creaky voice figured in the process of meaning-making and meaning negotiations throughout the conversation. Results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…While we are not advocating for HNR to be thought of as "an ironic voice quality", meaning that not everything that has low HNR will be ironic, we are suggesting that speakers use lowered HNR to differentiate their ironic utterances from regular, baseline, non-ironic utterances. To explain why speakers do this, we can turn to Bolyanatz (2023) who recently examined spontaneously occurring creaky voice in sociolinguistic interviews in Chilean Spanish. Bolyanatz (2023) determined that creak was primarily used to invoke alignment with the listener via ensuring that their messages or stances (Du Bois 2007) were understood and potentially endorsed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we are not advocating for HNR to be thought of as "an ironic voice quality", meaning that not everything that has low HNR will be ironic, we are suggesting that speakers use lowered HNR to differentiate their ironic utterances from regular, baseline, non-ironic utterances. To explain why speakers do this, we can turn to Bolyanatz (2023) who recently examined spontaneously occurring creaky voice in sociolinguistic interviews in Chilean Spanish. Bolyanatz (2023) determined that creak was primarily used to invoke alignment with the listener via ensuring that their messages or stances (Du Bois 2007) were understood and potentially endorsed.…”
Section: Discussionmentioning
confidence: 99%
“…To explain why speakers do this, we can turn to Bolyanatz (2023) who recently examined spontaneously occurring creaky voice in sociolinguistic interviews in Chilean Spanish. Bolyanatz (2023) determined that creak was primarily used to invoke alignment with the listener via ensuring that their messages or stances (Du Bois 2007) were understood and potentially endorsed. Similarly, we posit that the decreased HNR in the present study (which may signal either increased creaky or breathy phonation) found for syllables in all three subtypes of ironic utterances may serve the same purpose: that of aligning the speaker and hearer via a combination of humor and prosody.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this exclusion is two-fold: we were interested in obtaining clear H1-H2 cut-off points among modal, creaky, and breathy voice, which would be facilitated by longer analysis windows in FFT spectra. In addition, the 30% threshold has been used in other studies focusing on the analysis of creaky voice (Bolyanatz 2023), based on the fact that at least 30% of a vowel needs to have creak to be perceived as such utterance-finally (Crowhurst 2018). This resulted in the H1-H2 analysis of 549 phonation intervals (females, n = 354; males, n = 195).…”
Section: Methodsmentioning
confidence: 99%
“…This is often the case when Spanish is in a contact situation with a language that has phonological glottalization, such as Yucatec Maya, Guaraní, or Arabic (Thon 1989;Valentín-Márquez 2006;Chappell 2013;Michnowicz and Kagan 2016;McKinnon 2018;Mohamed et al 2019;Gynan and Almada 2020). Vowels can also have creaky voice word-finally in various dialects, including Peninsular, Chilean, and Mexican Spanish (Morrison and Escudero 2007;Garellek and Keating 2015;Bolyanatz 2023;cf. Kim 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that creak was more common among men than women, and with low vowels. Bolyanatz (2023) investigated the use of creaky voice in interview speech among 18 speakers of Chilean Spanish, and argued that 40% of highly creaky utterances are used for discourse-related purposes such as signaling conversational turns or uncertainty.…”
Section: Phrase-final Breath and Phrase-final Creakmentioning
confidence: 99%